ASSESSMENT OF MANAGEMENT EFFICIENCY IN COMPETITIVE PERSONNEL TRAINING (British Journal of Global Ecology and Sustainable Development, 2023)
The article covers the effectiveness of management activities of higher educational institutions, the effectiveness of management activities, the interaction and factors of the effectiveness of the management system and the management process, indicators of the effectiveness of the educational institution, and the issues of the priorities of the training departments.